A Simple and Effective Tool to Extrude Tropical Residual Soil Sample - Mohd Fakhrurrazi, Ishak; Mohammad Affendy, Omardin; M.H., Zainal Abidin; S.A., Ahmad Tajudin (IOP Publishing Ltd, 2017)
Soil Investigation is a vital part of a feasibility study of modern construction project and it helps to determine the types and characteristics for better construction planning. In orderto determine the types and characteristics of the soil lab tests must be conducted thus sampling of soil must be done. Sampling of tropical residual soil is vital and need a special care to extrude soil from sample casing. Traditional soil extruder and trimmer take some time to be done thus this project is done to propose a new soil extruder and trimmer that can get the job done easier, faster and also ensure the quality of the soil sample at the same time. This proposed equipment is a specially design to reduce and overcome disturbing of soil sample during extruding and trimming soil sample from thin wall tube including piston sampler. A part from that, the procedures to handle the tools will becomes easier and faster, especially on tropical residual soil that notoriously known as non-homogenous. Related to time consuming to prepared sample and effort to extrude it is conclude that the new proposed soil extruder is better than existing soil extruder.